2023
DOI: 10.1038/s41598-023-28922-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel versatile topologies and design optimization of wide-bandstop frequency selective surfaces for X-band, Ku-band and millimeter-wave applications

Abstract: Novel designs of frequency selective surface (FSS) are presented for wideband applications in X, Ku and mmWave (millimeter Wave) bands. Two identical metallic layers of FSS are imprinted on both sides of the RO4003 substrate. The geometry parameters are optimized to maximize the bandstop at the specified in-band maximum transmission level of −10 dB; satisfaction of the latter condition is enforced through appropriate formulation and handling of the design constraints. The proposed structure is versatile and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… Operating Freq. (in GHz) Type Mode Description 3 6.81–18.97 22.28–55.78 Passive Transmissive Wide-bandstop FSS resonating at X-band, Ku-band and millimeter-wave applications 5 4.8–11.1 Passive Reflective Ultra-broadband thin FSS based radar absorber 6 2.5 and 5.45 Passive Reflective Ultra-miniaturised Polarisation Selective Surface (PSS) for dual-band Wi-Fi and WLAN shielding applications 9 9.2 Active Transmissive Dynamic control of asymmetric EM wave transmission 10 8.61 and 11.33 Re-configurable Reflective + Transmissive Multi-functional re-configurable FSS 13 10 Re-configurable Reflective + Transmissive Tuneable and broadband absorber using a switchable transmissive/reflective FSS 14 2.5 Re-configurable Reflective + Transmissive Broadband Polarization-Insensitive Tunable FSS for Wideband Shielding 25 10 Active Reflective Analysis of a free-space N-path-modulated metasurface 26 2.3, 3.3, and 5 Active ...…”
Section: Time-modulated Metasurface For On-air Frequency Mixingmentioning
confidence: 99%
See 2 more Smart Citations
“… Operating Freq. (in GHz) Type Mode Description 3 6.81–18.97 22.28–55.78 Passive Transmissive Wide-bandstop FSS resonating at X-band, Ku-band and millimeter-wave applications 5 4.8–11.1 Passive Reflective Ultra-broadband thin FSS based radar absorber 6 2.5 and 5.45 Passive Reflective Ultra-miniaturised Polarisation Selective Surface (PSS) for dual-band Wi-Fi and WLAN shielding applications 9 9.2 Active Transmissive Dynamic control of asymmetric EM wave transmission 10 8.61 and 11.33 Re-configurable Reflective + Transmissive Multi-functional re-configurable FSS 13 10 Re-configurable Reflective + Transmissive Tuneable and broadband absorber using a switchable transmissive/reflective FSS 14 2.5 Re-configurable Reflective + Transmissive Broadband Polarization-Insensitive Tunable FSS for Wideband Shielding 25 10 Active Reflective Analysis of a free-space N-path-modulated metasurface 26 2.3, 3.3, and 5 Active ...…”
Section: Time-modulated Metasurface For On-air Frequency Mixingmentioning
confidence: 99%
“…A comparison of the developed multi-functional metasurface with recent literature is presented in Table 1. The studies referenced in 3,9,[25][26][27][28][29][30] present active/passive metasurfaces where 3,9,26,27 operate solely in transmissive mode whereas those in 25,[28][29][30] function exclusively in reflective mode. The studies in 10,13,14 present re-configurable FSSs operating in both transmissive and reflective modes.…”
Section: Variation Of Metasurface Bias Voltage ( V B )mentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20] In addition, the FSS has been studied by exploiting the material characteristics as detailed in Zhou et al 21 where graphene is used to enhance the FSS property. The FSS in other studies [22][23][24][25] has been demonstrated as a next-generation solution. Metaheuristic algorithms involving deep learning concepts have been reported in Mahouti et al 26 to efficiently design and optimize the FSS.…”
Section: Introductionmentioning
confidence: 99%